Henry and Ribsy - Cleary, Beverly (Henry Huggins., 2017)
Henry Huggins makes a deal with his father--if Henry can keep his dog Ribsy out of trouble for a month, he can go fishing with his father. Ribsy does his best to make Henry lose the deal.